O auxílio direto como instrumento de cooperação jurídica internacional em matéria de prova : uma análise da evolução jurisprudencial em face do CPC/2015 - Pimenta, Gabriela Galimberti De Souza (2019)
This work was based on the studies carried out by the research groups "International Law and the Codification Maze" and "Limits and Extension of the brazilian’s International Jurisdiction", led by Professor Valesca Raizer Borges Moschen in the stricto sensu postgraduate program in Procedural Law of the Federal University of the State of Espírito Santo. The research developed is inserted in the field of International Process and Constitutional Process, relating to the contemporary premises of International Law regarding human rights international protection, conventional and legal codifications harmonization, the development of international and domestic mechanisms aimed at implementing the jurisdictional protection of cross-border disputes, highlighting the evolution of international legal cooperation and its instruments. Faced with this situation, the dissertation developed should adopt as a premise the effectiveness of the jurisdictional protection of cross-border disputes, the scope for the welfare of protected life and the protection of the defendants rights and guarantees. In this context, the purpose of the dissertation is to understand the use of the direct aid as an autonomous instrument of international legal cooperation in the field of evidence, in the civil, commercial and criminal spheres, in the brazilians legal system. To this end, this study will seek to identify not only the mechanisms and procedures applicable to the chosen topic, but also the obstacles advocated in the jurisprudence of the brazilians High Courts, that must be overcome in order to guarantee the defendants full access to justice and due process of law with respect to border disputes. There will be a study of the jurisprudences evolution regarding the treatment given to direct aid as an international legal cooperation instrument in evidence matters, in conflict with the decisions handed down during the validity of the 1973’s and the 2015’s Civil Procedure Codes. Finally, this research will try to confirm or deny the hypothesis that the 2015’s Civil Procedure Code have solved the obstacles existing in the 1973 procedural system about the use of direct aid in proofs matter